Formation of the State budget in Finland: The best practices for Ukraine on the way to the EU membership - Kashevskaya, Galina V.; Komova, Olena S.; Pereguda, Yevgen V.; Glukh, Maryna V.; Tsurkanova, Iryna O. (P.A. Persona e Amministrazione, 2023)
The relevance of the study is stipulated by the need to carry out democratic reforms in Ukraine on the way to the EU membership. It is also obligatory for Ukraine to make a transparent system of government policies and laws, which has been under close attention of citizens and international stakeholders since February 24th, 2022 in conditions of unimagined financial support for Ukrainians on their heroic way to independence. Therefore, the aim of the study is to propose a method of economical-political analysis of the state budget with the help of a comparison of forming principles of revenues in Finland and Ukraine. These countries are interesting for this research because they are different in terms of their political system and the level of socio-economic development. However, a century ago both countries were parts of the Russian Empire. Finland is a member of the EU since 1996, while Ukraine is on the way to the EU membership. The article presents a method of analysis of the states’ budget revenues and draws conclusions about the democratic principles for a budget planning policy to ensure democracy and economic growth. The proposed methodology can be used by political and economic analysts, civil society activists and ordinary citizens interested in the issues of transparency and efficiency of the public administration system in their country. The work is practical in nature and is focused on giving a method of a state policies and laws analysis, and on increasing the political literacy of citizens to enable them to exercise the control of the own country and society development.